2005
DOI: 10.1111/j.1474-919x.2005.00379.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in egg size, shell thickness, pore density, pore diameter and water vapour conductance between first and second eggs of Snares Penguins Eudyptes robustus and their influence on hatching asynchrony

Abstract: Brood reduction in birds is frequently induced by hatching asynchrony. Crested penguins (genus Eudyptes) are obligate brood reducers, but in contrast to most other birds, first‐laid eggs are considerably smaller in size than second‐laid eggs; furthermore, first‐laid eggs hatch after their siblings. The mechanisms underlying this reversal in size and hatching order remain unclear. In this study, we tested whether the second‐laid eggs of Snares Penguins Eudyptes robustus have a higher eggshell porosity allowing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…Since later laying has often been associated with lower reproductive success as a result of declining food availability during the period of parental care (Norris 1993;Wiggins et al 1994), there may be a reproductive advantage for females breeding later in the season to reduce incubation time. It has been shown in numerous studies that total pore area of the eggshell affects water vapour conductance, and both of them are positively related to the growth rate of embryos and hatchability of eggs (Burton and Tullett 1983;Ar and Rahn 1985;Soliman et al 1994;Massaro and Davis 2005;Zimmermann and Hipfner 2007). In the Yellow-eyed Penguin, detected an increase in pore density with laying date which may allow embryos to develop more rapidly than earlier laid eggs.…”
Section: Discussionmentioning
confidence: 95%
“…Since later laying has often been associated with lower reproductive success as a result of declining food availability during the period of parental care (Norris 1993;Wiggins et al 1994), there may be a reproductive advantage for females breeding later in the season to reduce incubation time. It has been shown in numerous studies that total pore area of the eggshell affects water vapour conductance, and both of them are positively related to the growth rate of embryos and hatchability of eggs (Burton and Tullett 1983;Ar and Rahn 1985;Soliman et al 1994;Massaro and Davis 2005;Zimmermann and Hipfner 2007). In the Yellow-eyed Penguin, detected an increase in pore density with laying date which may allow embryos to develop more rapidly than earlier laid eggs.…”
Section: Discussionmentioning
confidence: 95%
“…Previous results from poultry and wild birds have indicated that eggshell breaking strength and/or eggshell thickness are influenced by the egg size and color (Kennedy and Vevers,'73), the location of the egg where these parameters are measured (Gosler et al, 2005), egg developmental stage (Vanderstoep and Richards, '70;Bunck et al, '85;Bennett, '95;Castilla et al, 2007), shell microstructure (Massaro and Davis, 2005), female age, body mass and health status, the time the eggs spend in the uterus, the length of incubation period, egg laying sequence and clutch number (Ar et al, '79;Massaro et al, 2002;Massaro and Davis, 2004;Castilla et al, 2009), the type of diet (Connor and Arnold,'72) and genetics (Francesch et al,'97).…”
mentioning
confidence: 97%
“…Among all populations of rockhopper penguins (Table 1), we similarly noted that the least dimorphic eggs were those from the Falkland Island population. In this study, the A-egg averaged 0.79 of the B-egg volume, a value between the Snares penguin and the Fiordland penguin species (0.77 and 0.85, respectively, Warham 1974a, b;Massaro and Davis 2005). This population has, therefore, the second least dimorphic eggs of all crested penguins after the Fiordland penguin.…”
Section: Intra-clutch Egg Dimorphism Between Speciesmentioning
confidence: 99%